1991
DOI: 10.1103/physrevd.44.2604
|View full text |Cite
|
Sign up to set email alerts
|

Momentum lattice simulation of theφ4model close to criticality

Abstract: We present results of a numerical simulation of the 44 model in the symmetric phase close to the critical line, using a momentum lattice and Langevin updating. We discuss how to extract physics from the zero-momentum behavior of the correlation function. As an example, we have computed mR and ZR and compared it with the analytical results of Liischer and Weisz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…It can be solved using a standard method like Euler's method where the truncation term is O(∆τ 2 ), or a higher order scheme like Heun's method (second order Runge-Kutta) where the truncation term is O(∆τ 3 ). Batrouni et al [1] have shown that a higher order integration scheme has many advantages, and our experience [3] agrees with theirs. For the same level of error, Heun's method is faster; it takes fewer "time" steps.…”
Section: Numerical Point Of Viewsupporting
confidence: 90%
See 4 more Smart Citations
“…It can be solved using a standard method like Euler's method where the truncation term is O(∆τ 2 ), or a higher order scheme like Heun's method (second order Runge-Kutta) where the truncation term is O(∆τ 3 ). Batrouni et al [1] have shown that a higher order integration scheme has many advantages, and our experience [3] agrees with theirs. For the same level of error, Heun's method is faster; it takes fewer "time" steps.…”
Section: Numerical Point Of Viewsupporting
confidence: 90%
“…This kind of behavior has not been seen in the φ 4 -model. The knowledge of the stability region is very important for simulations of theories like SU(2) and SU (3). For these models, the time needed for generating equilibrium configurations is much larger than for the U(1)-model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations